Custo-efetividade da espuma multicamadas de poliuretano com silicone comparada ao filme transparente de poliuretano na prevenção de lesão por pressão - Fonseca, Graziele Gorete Portella da (2018)
The cost-effectiveness evaluation consists of a process that aims to define, in an orderly and practical manner, the relationship between the cost and the benefits of a particular treatment for health. The objective was to conduct a cost-effectiveness analysis of multi-layer polyurethane foam with silicone and polyurethane clear film in the prevention of pressure injury in hospitalized patients of the intensive care unit. This is a complete economic study in which a cost-effectiveness analysis was performed through an economic modeling from the perspective of the SUS, with a time horizon of 30 days. Patients were hospitalized in the intensive care unit, and as technologies evaluated were polyurethane multilayer foam with silicone and transparent polyurethane film. The analysis, was performed through the decision tree, and the inputs for the construction of the model were derived from data from the literature. Cost-effectiveness analysis included incremental cost analysis, incremental effectiveness and incremental cost effectiveness. Sensitivity analyzes were all performed in TreeAge Pro 2017. As a result, it was obtained that patients submitted to transparent polyurethane film have a lower risk of developing heel pressure injury, in addition to promoting an average saving of R$ 203,19 for each patient exposed to the technology. The multivariate probabilistic sensitivity analysis demonstrated that polyurethane clear film should be considered as the first alternative for the prevention of heel pressure injury. The budget impact analysis showed that the use of transparent polyurethane film promotes a saving of R$ 243.816,00annually, compared to the use of polyurethane multilayer foam in the prevention of heel pressure injury.